Insights into the binding mode of AS1411 aptamer to nucleolin - Bie, Lihua; Wang, Yue; Jiang, Fuze; Xiao, Zhen; Zhang, Lianjun; Wang, Jing (Frontiers in Molecular Biosciences, 2022)
AS1411 aptamer can function as a recognition probe to detect the cell surface nucleolin overexpressed in cancer cells, however, little is known about their binding process. This study proposed a feasible binding mode for the first time and provided atomic-level descriptions for the high affinity and specific binding of AS1411. The binding pose predicted by docking was screened using knowledge-based criteria, and a microsecond molecular dynamics (MD) simulation showed the stable existence of the predicted structure in the solution. Structural analysis shows that the unique capping of the 5' end of AS1411 provides the specific binding with RBD1, and the interactions of hydrogen bond, salt bridge, and water-mediated network between AS1411 and RBD1,2 stabilize the binding. The calculation of per-residue decomposition emphasizes the dominant contribution of van der Waals energy and critical residues are screened. Our study provides the molecular basis of this specific binding and can guide rational AS1411-based aptamers design. Further insights require tight collaborations between the experiments and in silico studies.